Regulation of pacing strategy during athletic competition: evaluation of the hazard score hypothesis - Reinschmidt, Patrick (My University, 2018)
Regulation of energy expenditure is critical during endurance competition. The Hazard Score is a term that has been proposed to describe the likelihood that an athlete will decrease their velocity during the course of an endurance event, such as cycling or running. The Hazard Score is defined as the product of momentary Rating of Perceived Exertion (RPE) and the fractional distance remaining in the exercise bout. A higher Hazard Score is associated with a higher likelihood that an athlete will decrease velocity, while a low Hazard Score is associated with a higher likelihood that the athlete will increase velocity. Purpose: To determine the effect of a non-uniform pacing strategy utilizing two random 1-km bursts on Hazard Score and power output (PO) trends during 20-km cycling time trials. Methods: 10 subjects (8 males, 2 females) completed a maximal incremental exercise test, as well as one habituation, one steady state (SS) 20-km trial and two of four possible variations in non-uniform (BURST) pacing templates in order to compare the evolution of Hazard Score within trials. Each trial was separated by at least 48 hours. PO, heart rate (HR), and blood lactate were measured for each trial, as well as maximal oxygen consumption (VO2max) during the incremental test. RPE was recorded at the end of each kilometer using the Category Ratio scale of RPE. Regression analysis was used to examine the relationship between Hazard Score and subsequent change in the PO. Results: A moderate correlation (r=0.36) was found between Hazard Score and change in PO across all trials. No significant difference was found between Hazard Score evolution during STEADY STAT and BURST trials. Conclusion: This study showed that Hazard Score is a moderately effective predictor of PO changes during a 20-km cycling event when utilizing a non-uniform pacing template.
Keywords: Exercise -- Physiological aspects.; Cycling.; Exercise tests.